Have NEC Coat, Will Travel: Structural Basis of Membrane Budding During Nuclear Egress in Herpesviruses - Bigalke, J.M. (Adv Virus Res, 2016)
Herpesviruses are unusual among enveloped viruses because they bud twice yet acquire a single envelope. Furthermore, unlike other DNA viruses that replicate in the nucleus, herpesviruses do not exit it by passing through the nuclear pores or by rupturing the nuclear envelope. Instead, herpesviruses have a complex mechanism of nuclear escape whereby nascent capsids bud at the inner nuclear membrane to form perinuclear virions that subsequently fuse with the outer nuclear membrane, releasing capsids into the cytosol. This makes them some of the very few known viruses that bud into the nuclear envelope. The envelope acquired during nuclear budding does not end up in the mature viral particle but instead allows the capsid to translocate from the nucleus into the cytosol. The viral nuclear egress complex (NEC) is a critical player in the nuclear egress, yet its function and mechanism have remained enigmatic. Recent studies have demonstrated that the NEC buds membranes without the help of other proteins by forming a honeycomb coat, which established the NEC as the first virally encoded budding machine that operates at the nuclear, as opposed to cytoplasmic, membrane. This review discusses our current understanding of the NEC budding mechanism, with the emphasis on studies that illuminated the structure of the NEC coat and its role in capsid budding during herpesvirus nuclear escape.